Impact of climate variables to major food crops’ yield in midhills of western development region, Nepal - Aryal, M; Regmi, PP; Thapa, RB; Pande, KR; Pant, KP (Journal of Agriculture and Environment, 2018)
Climate change is threatening the agriculture sector especially on present and future food security in low income countries. Primary and secondary data collected through household survey and collected from different secondary source were used to assess the effects of climate variables on crop yield and the uniformity of effects across crops and growing seasons in Kaski district considering six major food crops as paddy, maize, wheat, millet, Barley and potato. A multivariate regression analysis, based on the first difference time series of crop yield and climate variables, is employed to estimate the empirical relationships between crop yield and climate variables. The results are discussed at district level empirically. It showed that climate variables significantly influence the crop yield, but not uniformly on all crops and in all growing seasons.